Internalization of trophoblastic small extracellular vesicles and detection of their miRNA cargo in P-bodies. Issue 1 (1st January 2020) - Li, Hui; Pinilla-Macua, Itziar; Ouyang, Yingshi; Sadovsky, Elena; Kajiwara, Kazuhiro; Sorkin, Alexander; Sadovsky, Yoel
ABSTRACT: Pregnancy is a unique situation, in which placenta-derived small extracellular vesicles (sEVs) may communicate with maternal and foetal tissues. While relevant to homoeostatic and pathological functions, the mechanisms underlying sEV entry and cargo handling in target cells remain largely unknown. Using fluorescently or luminescently labelled sEVs, derived from primary human placental trophoblasts or from a placental cell line, we interrogated the endocytic pathways used by these sEVs to enter relevant target cells, including the neighbouring primary placental fibroblasts and human uterine microvascular endothelial cells. We found that trophoblastic sEVs can enter target cells, where they retain biological activity. Importantly, using a broad series of pharmacological inhibitors and siRNA-dependent silencing approaches, we showed that trophoblastic sEVs enter target cells using macropinocytosis and clathrin-mediated endocytosis pathways, but not caveolin-dependent endocytosis. Tracking their intracellular course, we localized the sEVs to early endosomes, late endosomes, and lysosomes. Finally, we used coimmunoprecipitation to demonstrate the association of the sEV microRNA (miRNA) with the P-body proteins AGO2 and GW182. Together, our data systematically detail endocytic pathways used by placental sEVs to enter relevant fibroblastic and endothelial target cells, and provide support for "endocytic escape" of sEV miRNA to P-bodies, a key site for cytoplasmic RNA regulation.